MALIK BADRI, SPREADER OF LIGHT FROM SUDAN - Trimulyaningsih, Nita; Nashori, Fuad (Psikis : Jurnal Psikologi Islami, 2022)
At the end of the 20th century, a new scientific movement emerged in psychology called Islamic Psychology. Islamic psychology emphasizes the view of fitrah (sacred nature) in science. This science began when a book entitled "The Dilemma of Muslim Psychologists" was published, inspired, and awakened Muslim scientists in the world to return to the truth of Islam in psychology. The book was written by Malik Badri, who is known as the Father of Islamic Psychology. Seeing how big the role of Malik Badri in Islamizing psychology is, the researcher wanted to get a clear description of Malik Badri's biography, including the style of thought and the work produced. To get a biographical article, the researcher reviewed the literature/documents about Malik Badri like books, journals, news, and others about Malik Badri’s biography, creation, thought, etc with the design of a narratively qualitative approach. The data collected were analyzed by restorying stories. The result showed that there were so many contributions of Malik Badri for his discipline and also in the world society.